2023
DOI: 10.32385/rpmgf.v39i1.13494
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus não controlada: inércia vs adesão à terapêutica

Abstract: Introdução: Em Portugal, a taxa de não controlo dos pacientes com diabetes é de cerca de 35%. De entre as causas descritas como barreiras ao alcance dos objetivos no controlo dos doentes diabéticos salientam-se a inércia terapêutica e a má adesão à terapêutica. Objetivos: Calcular a proporção de utentes com diabetes mellitus (DM) não controlada na USF Garcia de Orta e analisar a distribuição dos valores da hemoglobina glicada (HbA1c). Calcular a proporção de má adesão e de inércia terapêutica nos pacientes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…11,28 Other authors have not found an association with this study variable. 9,24,26 No association was observed with the other patient and healthcare professional variables, such as training in diabetes mellitus and length of service, which is similar to what has been reported in the literature, 9,16,23 but contrary to what was found in another study conducted in a primary care health center. 27 One of the limitations of this research was its design, as it is a crosssectional study, it is subject to possible selection bias, as those who came for medical advice may have been motivated by lack of economic resources or discomfort.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…11,28 Other authors have not found an association with this study variable. 9,24,26 No association was observed with the other patient and healthcare professional variables, such as training in diabetes mellitus and length of service, which is similar to what has been reported in the literature, 9,16,23 but contrary to what was found in another study conducted in a primary care health center. 27 One of the limitations of this research was its design, as it is a crosssectional study, it is subject to possible selection bias, as those who came for medical advice may have been motivated by lack of economic resources or discomfort.…”
Section: Discussionsupporting
confidence: 68%
“…21 The frequency of therapeutic inertia observed in this study in both genders was higher than that reported by various authors at international and national levels. 9,16,[22][23][24][25][26][27] These differences may be explained by the nature of the population, the inclusion criteria used, the epidemiologic design, and the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…21 La frecuencia de inercia terapéutica observada en esta investigación para ambos sexos fue mayor a la referida por diversos autores a nivel internacional y nacional. 9,16,[22][23][24][25][26][27] Estas diferencias pueden ser explicadas por el tipo de población, los criterios de inclusión utilizados, el diseño epidemiológico y el tamaño de la muestra.…”
Section: Discussionunclassified
“…11,28 Otros autores no identificaron relación con dicha variable de estudio. 9,24,26 No se observó asociación con el resto de las variables del paciente y el personal médico como la capacitación recibida en temas relacionados con diabetes mellitus y su antigüedad laboral lo cual es similar a lo referido en la literatura, 9,16,23 pero contrario a lo encontrado en otro estudio realizado en un centro de salud de atención primaria. 27 Una de las limitaciones de esta investigación fue el diseño, al ser un estudio transversal está sujeto a posibles sesgos de selección, ya que quienes acudieron a consulta médica posiblemente fueron motivados por la falta de recursos económicos o malestares.…”
Section: Discussionunclassified